2019
DOI: 10.1136/bcr-2018-229012
|View full text |Cite
|
Sign up to set email alerts
|

Congenital chloride diarrhoea

Abstract: Congenital chloride diarrhoea is one of the rare causes of diarrhoea during infancy and it is infrequently reported throughout the world. It is an autosomal recessive condition which is more prevalent in Poland, Finland, Saudi Arabia and Kuwait while rarely reported in Pakistan. Our patient was 7.5-month-old baby boy who presented with diarrhoea since neonatal period. He had consanguineous parents. On examination, baby had distended abdomen, hypotonia and hyporeflexia. Investigations revealed hypochloremic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The contents of the distal small intestinal cavity generally show high signals on the T1W sequence, and the intensity is consistent with meconium. [7][8][9] After ultrasound examination, this case showed polyhydramnios and intestinal dilation, making it difficult to make a definite diagnosis. A further MRI was performed using a Siemens Magnetom Skyra 3.0T MRI scanner using the sequence T2 weighted half-Fourier acquisition single-shot turbo-spin-echo (HASTE), T2 weighted true steady-state precession rapid imaging (TrueFISP), and T1 weighted multiecho water and fat separation imaging (Dixon).…”
Section: Discussionmentioning
confidence: 95%
“…The contents of the distal small intestinal cavity generally show high signals on the T1W sequence, and the intensity is consistent with meconium. [7][8][9] After ultrasound examination, this case showed polyhydramnios and intestinal dilation, making it difficult to make a definite diagnosis. A further MRI was performed using a Siemens Magnetom Skyra 3.0T MRI scanner using the sequence T2 weighted half-Fourier acquisition single-shot turbo-spin-echo (HASTE), T2 weighted true steady-state precession rapid imaging (TrueFISP), and T1 weighted multiecho water and fat separation imaging (Dixon).…”
Section: Discussionmentioning
confidence: 95%
“…El contenido de intestino delgado distal en general muestra señales hiperintensas en la secuencia T1W, correspondiente a la presencia de meconio. [7][8][9] En este caso, el examen por ultrasonido mostró polihidramnios y dilatación intestinal lo que dificultó el diagnóstico definitivo. Se realizó una RM con un equipo Siemens Magnetom Skyra 3.0T.…”
Section: Discussionunclassified
“…By a literature review performed on PUBMED and EMBASE, the effect of butyrate therapy has been reported in 18 CLD patients so far ( 4 , 8 , 10 , 12 , 14 , 16 19 ) ( Table 2 ). Just one patient was successfully treated by a step-up therapeutic approach, whereas to the other 17 patients butyrate therapy was administered starting with 100 mg/kg/day and they presented conflicting responses, and a possible genotype dependent response has been suggested ( 4 , 8 ).…”
Section: Discussionmentioning
confidence: 99%